2005
DOI: 10.1542/peds.2004-0815h
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Reported Sleep Quality and Sleep Hygiene in Italian and American Adolescents

Abstract: Objective-The purpose of the study was to examine the relationship between self-reported sleep quality and sleep hygiene in Italian and American adolescents and to assess whether sleephygiene practices mediate the relationship between culture and sleep quality.Methods-Two nonprobability samples were collected from public schools in Rome, Italy, and Hattiesburg, Mississippi. Students completed the following self-report measures: Adolescent Sleep-Wake Scale, Adolescent Sleep Hygiene Scale, Pubertal Developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
375
2
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(405 citation statements)
references
References 43 publications
15
375
2
13
Order By: Relevance
“…40 Previously good sleep routine has been shown to have a positive effect on sleep quality. 41 This model indicated that sleep routine and restless sleep completely mediate the relationship between caffeine consumption and morning tiredness but only partially mediated the relationship between morning tiredness and internalizing behaviors. This is important because it gives further insight into the importance of sleep and further understanding of the effect of caffeine on the relationship between sleep and behavior in children.…”
Section: Discussionmentioning
confidence: 93%
“…40 Previously good sleep routine has been shown to have a positive effect on sleep quality. 41 This model indicated that sleep routine and restless sleep completely mediate the relationship between caffeine consumption and morning tiredness but only partially mediated the relationship between morning tiredness and internalizing behaviors. This is important because it gives further insight into the importance of sleep and further understanding of the effect of caffeine on the relationship between sleep and behavior in children.…”
Section: Discussionmentioning
confidence: 93%
“…[17][18][19] The types of circadian preference are intrinsic and heritable characteristics of the individual associated with differences in habits, performance rhythms, physiological, and behavioral variables. 20 According to the literature, M-type individuals wake up early in the morning, fall asleep at an early hour and prefer early morning activities, while E-types seem to have problems waking up in the morning (e.g., need to be waked up by parents), 20,21 staying awake during the day (especially during school time), and feeling more exhausted during the day. 20,22 Circadian preference changes from preadolescence and adolescence, when a consistent shift to evening preference has been reported.…”
Section: Brief Summarymentioning
confidence: 99%
“…However, there is an increasing body of literature regarding the psychological and physiological differences between insomniacs and good sleepers. Several studies have demonstrated a greater prevalence of intrusive thoughts, worry, and rumination [8], poor sleep hygiene [9,10], dysregulation of the hypothalamic pituitary axis [11], elevations in sympathetic activity [12], and metabolic rate [13], increased daytime alertness [14], and elevated high-frequency electroencephalographic (EEG) activity [15][16][17] in patients with insomnia compared to good sleepers.…”
Section: Introductionmentioning
confidence: 99%